Progesterone: therapeutic opportunities for neuroprotection and myelin repair - Schumacher, Michael (2007)
Progesterone and its metabolites promote the viability of neurons in the brain and spinal cord. Their neuroprotective effects have been documented in different lesion models, including traumatic brain injury (TBI), experimentally induced ischemia, spinal cord lesions and a genetic model of motoneuron disease. Progesterone plays an important role in developmental myelination and in myelin repair, and the aging nervous system appears to remain sensitive to some of progesterone's beneficial effects. Thus, the hormone may promote neuroregeneration by several different actions by reducing inflammation, swelling and apoptosis, thereby increasing the survival of neurons, and by promoting the formation of new myelin sheaths. Recognition of the important pleiotropic effects of progesterone opens novel perspectives for the treatment of brain lesions and diseases of the nervous system. Over the last decade, there have been a growing number of studies showing that exogenous administration of progesterone or some of its metabolites can be successfully used to treat traumatic brain and spinal cord injury, as well as ischemic stroke. Progesterone can also be synthesized by neurons and by glial cells within the nervous system. This finding opens the way for a promising therapeutic strategy, the use of pharmacological agents, such as ligands of the translocator protein (18 kDa) (TSPO; the former peripheral benzodiazepine receptor or PBR), to locally increase the synthesis of steroids with neuroprotective and neuroregenerative properties. A concept is emerging that progesterone may exert different actions and use different signaling mechanisms in normal and injured neural tissue.